Outcomes of Irish graduate entry medical student engagement with self-directed learning of clinical skills - McGrath, Deirdre (BMC Med Educ, 2015)
BACKGROUND: Existing literature is mixed as to whether self-directed learning (SDL) delivers improvements in knowledge, skills or attitudes of medical students compared with traditional learning methods. This study aimed to determine whether there is an association between engagement in SDL and student performance in clinical examinations, the factors that influence student engagement with SDL in clinical skills, and student perceptions of SDL. METHODS: A retrospective analysis of electronic records of student bookings of SDL sessions from 2008 to 2010 was performed for students in the pre-clinical years of an Irish Graduate Entry Medical programme to assess their level of engagement with SDL. The extent to which this engagement influenced their performance in subsequent summative examinations was evaluated. A cross-sectional survey of students across the four years of the programme was also conducted to determine student perceptions of SDL and the factors that affect engagement. RESULTS: The level of engagement with SDL decreased over time from 95% of first years in 2008 to 49% of first years in 2010. There was no significant difference between the median exam performance for any clinical skills tested by level of engagement (none, one or more sessions) except for basic life support in first year (p =0.024). The main reason for engaging with SDL was to practice a clinical skill prior to assessment and the majority of respondents agreed that SDL sessions had improved their performance of the specific clinical skills being practised. CONCLUSION: Students viewed SDL as an opportunity to practise skills prior to assessment but there were no significant differences in subsequent summative assessment by the level of engagement for most clinical skills.